Unmasking the culprits of ocular motor nerve palsies - Ganiger, Arpita; Bellary, Radhika; Channashetti, Gajanan (International Journal of Research in Medical Sciences, 2025)
Background: The objective of the study was to describe the clinical, demographic, and etiological profile of patients with symptoms of acquired ocular motor palsy presenting to tertiary care centre at Gadag. Methods: 25 consecutive patients with symptoms of ocular motor nerve palsies visiting ophthalmology outpatient department (OPD) were investigated. All underwent complete ophthalmological examination. Imaging studies of the brain and laboratory tests were performed for all the patients. Results: Out of 25 patients, sixth cranial nerve palsy was seen in 16 patients. Rest of the 9 patients had pupil sparing 3rd nerve palsy, of which 2 had partial ptosis. Overall, an etiological diagnosis was made in 22 cases. 21 patients had vascular cause. One patient aged 24 years had cavernous sinus haemangioma. Computed tomography (CT) scan failed to reveal any abnormality in 3 cases. Conclusion: Ocular motor nerve palsy may be obvious or sub-clinical. Multisystemic approach is needed in these patients. Careful clinical examination and prompt investigations aids in early diagnosis and management.